G‐Protein‐Coupled Receptor Heteromers as Key Players in the Molecular Architecture of the Central Nervous System. (9th May 2014) - Brugarolas, Marc; Navarro, Gemma; Martínez‐Pinilla, Eva; Angelats, Edgar; Casadó, Vicent; Lanciego, José L.; Franco, Rafael
Summary The overall architecture of the nervous system, especially the CNS, is remarkable. The anatomy of the nervous system is constituted not only by macroscopic and microscopy identifiable regions and neuronal cell types, but also by protein complexes whose identification and localization require sophisticated techniques. G‐protein‐coupled receptors (GPCRs) constitute an example of proteins that are the key factors in the framework needed to sustain brain and nerve structure and function. The versatility underlying nervous system anatomy takes advantage of a recently discovered feature of GPCRs, the possibility to form heteromers that, placed at specific neuronal subsets and at specific locations (pre‐, post‐, or peri‐synaptic), contribute to attain unique neural functions.